DOI: 10.47749/t/unicamp.2009.465934
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do treinamento com pesos sobre a densidade mineral ossea, força muscular e variaveis funcionais na menopausa

Abstract: This study examined the adaptive responses of indicators of strength, bone mineral density (BMD), the resting metabolic rate (RMR) and aerobic capacity ( O 2 max and anaerobic threshold) after 16 weeks intervention resistance training program (RT). Participated 22 postmenopausal women (12 months without menstruation), subdivided in two groups: trained group (GT n = 12) and control group (GC n = 10). The RT period had frequency of three sessions per week on alternate days, with 10 exercises for upper limbs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…Several studies have used different concurrent training (CT) strategies to investigate the responses of this training in the human body, among them, there are studies comparing the effects of CT on the functional autonomy of elderly practitioners and non-practitioners (NUNES-JUNIOR, 2010), on strength and body composition in postmenopausal women (BONGANHA et al, 2008), on waist circumference (WC) and resting metabolic rate in menopausal women (ROSSI et al, 2013), on biochemical parameters, cardiovascular fitness, neuromuscular and WC in elderly women (CAMPOS et al, 2013), in maximum strength, anaerobic threshold and oxygen consumption (VO2peak) in middle-aged men (LIBARDI, 2011), in strength and balance gains in elderly women (DEL PONTE, 2013), in exercise variation and aerobic intensity in the cardiorespiratory and neuromuscular responses of young women (SILVA, 2010) and in muscle activation and strength, hormonal concentrations and endurance capacity in elderly men (CADORE, 2009).…”
Section: Effects Of Concurrent Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have used different concurrent training (CT) strategies to investigate the responses of this training in the human body, among them, there are studies comparing the effects of CT on the functional autonomy of elderly practitioners and non-practitioners (NUNES-JUNIOR, 2010), on strength and body composition in postmenopausal women (BONGANHA et al, 2008), on waist circumference (WC) and resting metabolic rate in menopausal women (ROSSI et al, 2013), on biochemical parameters, cardiovascular fitness, neuromuscular and WC in elderly women (CAMPOS et al, 2013), in maximum strength, anaerobic threshold and oxygen consumption (VO2peak) in middle-aged men (LIBARDI, 2011), in strength and balance gains in elderly women (DEL PONTE, 2013), in exercise variation and aerobic intensity in the cardiorespiratory and neuromuscular responses of young women (SILVA, 2010) and in muscle activation and strength, hormonal concentrations and endurance capacity in elderly men (CADORE, 2009).…”
Section: Effects Of Concurrent Trainingmentioning
confidence: 99%
“…In addition, the study by Bonganha et al (2008), used 10 weeks of CT to compare the results in muscle strength, flexibility and body composition of postmenopausal women who were or were not undergoing hormone replacement therapy, dividing 18 volunteers into a group with therapy (n =8) and group without therapy (n=10), participants performed 3 CT sessions per week, the sessions were composed of weight training and aerobic training, at the end of the study increases were observed in indicators of maximum muscular strength (1 -RM) without significant difference between the groups, but with a significant difference between the pre-and post-intervention moments. In the assessment of flexibility, the groups showed a significant increase only in the Wells bench test.…”
Section: Effects Of Concurrent Trainingmentioning
confidence: 99%
See 2 more Smart Citations